05.11 Antisense long noncoding rnas are deregulated in skin tissue of ssc patients. (1st March 2017) - Messemaker, Tobias; Chadli, Loubna; Goelela, Varshna; Boonstra, Maaike; Dorjee, Annemarie; Andersen, Stefan; Mikkers, Harald; Distler, Oliver; Huizinga, Tom; Li, Zhenghui; Cai, Guoshuai; Whitfield, Michael; et al.
Abstract : Background: Systemic sclerosis (SSc) is an autoimmune disease characterised by fibrosis of skin and multiple organs of which pathogenesis is poorly understood. Here we studied differentially expressed coding and non-coding genes in relation to SSc pathogenesis with a specific focus on antisense non-coding RNAs. Materials and methods: Skin biopsy-derived RNAs from fourteen early SSc patients and six healthy individuals were sequenced with ion-torrent and analysed using DEseq2. Protein-coding and non-coding genes annotated in GENCODEV7 were analysed. Significant long non-coding RNAs were independently replicated in a Northern American dataset. Results: 4901 genes with a fold change >1.5 and a false discovery rate of less than 5% were detected in patients versus controls. Upregulated coding genes clustered in immunological, cell adhesion and keratin-related processes as previously found by microarray studies. Interestingly, 676 deregulated non-coding genes were detected, 257 of which were classified as antisense genes. 42% of these antisense genes had a concurrent deregulated sense gene. The majority of the sense-antisense genes had a similar effect sizes in an independent North American dataset with three genes (OTUD6B-AS1, CTBP1-AS2 and HMGN3-AS1) exceeding the study-wide Bonferroni-corrected ρ-value (PBonf <0.0024, Pcombined =1.6×10 -9, 1.7 × 10 –6, 2.6 × 10 –6, respectively). Intriguingly, the correlation of sense-antisense gene pairs deregulated in SSc is stronger than sense-antisense gene pairs not deregulated in SSc (p<0.001). Conclusions: For the first time we highlight that together with coding genes, (antisense) long noncoding RNAs are deregulated in skin tissue of SSc patients suggesting a novel class of genes involved in pathogenesis of SSc.